Transcytosis route mediates rapid delivery of intact antibodies to draining lymph nodes - Kähäri L; Fair-Mäkelä R; Auvinen K; Rantakari P; Jalkanen S; Ivaska J; Salmi M (My University, 2022)
Lymph nodes (LNs) filter lymph to mount effective immune responses. Small soluble lymph-borne molecules from the periphery enter the draining LNs via a reticular conduit system. Intact antibodies and other larger molecules, in contrast, are physically unable to enter the conduits, and they are thought to be transported to the LNs only within migratory DCs after proteolytic degradation. Here, we discovered that lymph-borne antibodies and other large biomolecules enter within seconds into the parenchyma of the draining LN in an intact form. Mechanistically, we found that the uptake of large molecules is a receptor-independent, fluid-phase process that takes place by dynamin-dependent vesicular transcytosis through the lymphatic endothelial cells in the subcapsular sinus of the LN. Physiologically, this pathway mediates a very fast transfer of large protein antigens from the periphery to LN-resident DCs and macrophages. We show that exploitation of the transcytosis system allows enhanced whole-organ imaging and spatially controlled lymphocyte activation by s.c. administered antibodies in vivo. Transcytosis through the floor of the subcapsular sinus thus represents what we believe to be a new physiological and targetable mode of lymph filtering.